Agency and Structure Revisited with Youth Responses to Gendered (Spatial) Mobilities in the EU - Samuk Carignani, Şahizer; Schlimbach, Tabea; Kmiotek-Meier, Emilia; Diaz, Celia; Diaz Chorne, Laura; Vysotskaya, Volha; Nienaber, Birte; Roman, Monica; Muresan, Laura; Manafi, Ioana; Däubler, Markus (Border Crossing, 2020)
Young people involved in geographical mobility face diverse gendered mobility settings and gender inequalities. How do the youth involved in diverse mobility types deal with adverse circumstances caused by gender beliefs and gender prejudices? To answer this question, problem-centred interviews with young people (18-29) are analysed using Grounded Theory. These young people are European citizens and they are involved in five mobility types: higher education, employment, voluntary work, vocational education & training, and entrepreneurship. We apply Emirbayer and Mische’s (1998) categories (iterational, projective and practical-evaluative) to the analysis of gendered mobility narratives as unequal gender perceptions reveal themselves in the context of different types of youth mobility. The analysis allows to see the ways young people reflect on their actions: refusal of gender beliefs, acceptance or rejection of gendered prejudices, individual vs. collective solutions, demand for equality in numbers, comparison of gendered workplaces and assumption of leadership in initiating mobility. At the same time, we observe how geographical mobilities can increase the critical sensibility of youth towards gender inequalities, contributing to new conceptualisation of agentic responses to structural constraints.